Subgroups and Orbits by Companion Matrix in Three Dimensional Projective Space - Emad Bakr Al-Zangana; Nada Yassen Kasm Yahya (مجلة بغداد للعلوم)
The aim of this paper is to construct cyclic subgroups of the projective general linear group over  from the companion matrix, and then form caps of various degrees in . Geometric properties of these caps as secant distributions and index distributions are given and determined if they are complete. Also, partitioned of  into disjoint lines is discussed.